Role of Police relating to Safe Custody in Bangladesh: A Study from Human Rights Perspective - Islam, Md Nahidul; Miazi, Md Abu Nayem (Green University Review of Social Sciences, 2022)
This paper essentially provides a very clear understanding of the function of the police by highlighting specific domestic laws, a number of pertinent international instruments, as well as the fundamental human rights standard of safe custody in relation to human rights. The paper attempts an effort to conduct a documentary analysis of the role of police in relation to safe custody and human rights in Bangladesh's criminal justice system. Finally, the purpose of this paper is to highlight the real-world situation and activities of the police in advancing democracy in a developing country like Bangladesh. Green University Review of Social Sciences Dec 2021; 7(1-2): 130-154